Condições de vida e saúde de ribeirinhos da Floresta Nacional de Pau Rosa, Maués Amazonas - Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This work aimed to describe the living and health conditions of riverside dwellers in the communities of the Pau Rosa National Forest. This is a cross-sectional study conducted with riverside dwellers living in the Pau Rosa National Forest, municipality of Maués, from September to December 2019. 123 adult citizens of both sexes attended the study. Data analysis was performed using descriptive statistics. The results indicated that most interviewed people were female (73.17%), with up to 4 years of schooling (59.3%), the monthly family income is less than the minimum wage (56.9%). Agriculture and fishing represented the predominant occupational activities among riverside dwellers. The communities have shortages concerning drinking water supply and an adequate destination for domestic sewage, with the predominant use of rudimentary septic tanks. Among the self-reported health problems, anemia (68.2%), urinary tract infection (36.6%), hypertension (34.9%), rheumatism (18.7%), and diabetes (12.2%) stood out. The diet is characterized by two main foods, fish and cassava flour. The main resources used in health care were homemade medicines, due to the difficulties in getting health services. The transport used to reach the health services is the recreational boat 52%, the stern boat 41.5%, and the speedboat 6.5%. The journey time depends on the type of vessel and the power of the engine, on average the riverside inhabitants of Flona take more than 6 hours and cover 100 km to reach the municipality of Maués seat. The health professionals most sought-after by riverside dwellers in case of illness are healers 38.5%, Community Health Agents 35.5%, and doctors 17%. Among those interviewed, 71% reported having consulted a doctor in the last 12 months, and 44% went to the dentist in the last 3 years. Riverside dwellers navigate an average of 100 km and take about 8.2 hours to access the city's urban area, which represents difficulty in accessing health services. Geographical limitations that constitute barriers to accessing health services and improving the living conditions of riverside dwellers can limit the acquisition of epidemiological information on these populations and cause negative impacts on their life quality.
Keywords: Indicadores de saúde - Maués (AM); Serviços de saúde comunitária - Maués (AM); CIENCIAS DA SAUDE; Condições de saúde; Ribeirinhos; Comunidades; Amazônia; Florestas Nacionais